Ultra-Performance Liquid Chromatography (UPLC) in Analytical Method Development and Validation Following In-vitro Studies: Review Article (Journal of Pharma Insights and Research, 2025)
Ultra-performance liquid chromatography (UPLC) has emerged as a powerful analytical tool, offering superior resolution, sensitivity, and rapid analysis compared to conventional high-performance liquid chromatography. The integration of UPLC with advanced detection systems, particularly mass spectrometry, has transformed pharmaceutical research, biomarker discovery, and metabolomics studies. Recent innovations in column technology, including sub-2-micron particles and core-shell materials, have significantly enhanced separation efficiency and detection limits. UPLC plays a crucial role in drug metabolism studies, stability assessments, and bioactive compound quantification following in vitro experiments. The technique has proven invaluable in toxicology studies, enabling precise identification and quantification of metabolites in biological matrices. Method validation parameters for UPLC ensure reliable and reproducible results, encompassing specificity, linearity, accuracy, precision, and stability studies. Notable applications include rapid metabolite profiling, protein characterization in biopharmaceuticals, and biomarker identification in disease diagnosis. Despite challenges such as operational costs and complex sample preparation requirements, ongoing technological advancements in microfluidics, artificial intelligence integration, and green chromatography techniques continue to expand UPLC capabilities.